Being Entrapped Between Change and Return to the Kemalist Political Culture: Two Stories of the Ak Party Foreign Policy in the Context of Arab Spring - Rıdvan KALAYCI; Ünal TÜYSÜZ (Gazi Akademik Bakış)
This study is about foreign policy implementations that applied to design Turkish politics before and after the Arab Spring periods by Ak Party, which entered the political scene with the wind of “change” and “reform”. In this context, the current study suggests that the AK Party, prior to the Arab Spring, reinterpreted the basic paradigms of the Kemalist political culture and shaped its foreign policy on these dynamics, but with the Arab Spring, experienced a shift towards the traditional line. In order to embody this argument, the relationship between political culture and foreign policy in the AK Party period is examined in detail.